The role of duty, gender and intergenerational care in grandmothers' parenting of grandchildren: a phenomenological qualitative study - José Miguel Mansilla-Domínguez; Ana María Recio-Vivas; Laura Lorenzo-Allegue; José Miguel Cachón-Pérez; Laura Esteban-Gonzalo; Domingo Palacios-Ceña (BMC, 2024)
Abstract Objectives The aim of this study was to describe grandmothers' experiences of taking care of their grandchildren in terms of their care-giving tasks, motivations and emotions. Methods A qualitative phenomenological study was conducted. Purposive sampling was used, based on the relevance of the research question. Seventeen participants were included, women ≥ 65 years old, grandmothers who care for their grandchildren at least 10 h per week and who attended the Nursing units of the Primary Care Health Centers (Madrid Public Health Service). Seventeen in-depth interviews were conducted. The interviews were audio-recorded, transcribed verbatim and thematic analysis was carried out from the perspective of hermeneutic phenomenology. For the analysis, the Excel program was used to organize and share the coding process. Also, we followed COREQ guidelines. Results Four main themes were identified: (a) Care out of obligation, where participants feel an obligation to help their children by caring for grandchildren, regardless of their number, and prefer to do so voluntarily; (b) Care out of responsibility, where grandmothers see their role as a responsibility that includes saving costs by caring for grandchildren and facilitating their children's work life balance; (c) Care as a social duty, reflecting a moral commitment inherited from their mothers to help future generations; and (d) Construction of care from a gender perspective, where grandmothers, as women, primarily assume the care and upbringing of grandchildren. Discussion Our results contribute to increase knowledge about childcare provided by grandmothers to their grandchildren. Grandmothers become fundamental pillars of families by helping their children balance family and work. Behind this care there is a strong sense of obligation, duty and generational responsibility. Grandmothers' help presents differences in the distribution of tasks and care by sex. Identifying factors that motivate grandmothers to care for their grandchildren helps nurses to perform higher quality comprehensive care.